Criminal thinking styles and emotional intelligence in Egyptian offenders. (25th January 2013) - Megreya, Ahmed M.
Abstract Background The Psychological Inventory of Criminal Thinking Styles (PICTS) has been applied extensively to the study of criminal behaviour and cognition. Increasingly growing evidence indicates that criminal thinking styles vary considerably among individuals, and these individual variations appear to be crucial for a full understanding of criminal behaviour. Aims This study aimed to examine individual differences in criminal thinking as a function of emotional intelligence. Methods A group of 56 Egyptian male prisoners completed the PICTS and Bar‐On Emotional Quotient Inventory (EQ‐i). The correlations between these assessments were examined using a series of Pearson correlations coefficients, with Bonferroni correction. Results General criminal thinking, reactive criminal thinking and five criminal thinking styles (mollification, cutoff, power orientation, cognitive indolence and discontinuity) negatively correlated with emotional intelligence. On the other hand, proactive criminal thinking and three criminal thinking styles (entitlement, superoptimism and sentimentality) did not associate with emotional intelligence. Conclusions Emotional intelligence is an important correlate of individual differences in criminal thinking, especially its reactive aspects. Practical implications of this suggestion were discussed. Copyright © 2013 John Wiley & Sons, Ltd.